Kobiety w procesie cz. I – kobiety przed sądem - Łaszewska-Hellriegel, Martyna; Mecke, Christoph Eric (PRAWO i WIĘŹ, 2024)
This paper is the first part of the topic on the position of women in the judicial process in Poland and Germany. It examines the legal position of women in court in Polish and German legal history from the 16th to the 20th century. The study distinguishes between criminal and civil proceedings, between unmarried and married women and merchant women, and between land, town and village law in Poland and ius commune, special and local law in Germany. While women were treated similarly to men in criminal proceedings at the beginning of the sixteenth century, there were major differences in civil proceedings. In both Poland and Germany, the unequal treatment of men and unmarried women ended around 1800 as a result of European codification. In contrast, married women had to wait until the 20th century for equal rights, even in court.